"Reactance inversion" at low frequencies during lung function measurement by impulse oscillometry in children with persistent asthma#. (3rd August 2022) - González Vera, Ramiro; Vidal Grell, Alberto; Yarur, Alejandra Mendez; Meneses, Constanza Olivares; Castro-Rodriguez, Jose A.
Abstract: Background: Small airway dysfunction (SAD) in asthma can be measured by impulse oscillometry (IOS). Usually, the reactance should decrease with decreases in frequency oscillation. Sometimes an upward shift of the curve at low frequencies can be observed together with lower than expected reactance values. The actual value of the reactance at 5 Hz (X5) is calculated by the Sentry Suite application of the Jaeger Master screen iOS system™, providing the corrected X5 parameter (CX5). Our hypothesis is that correction of X5 is common in persistent asthma and it correlates better than X5 with the IOS parameters for evaluating SAD. Methods: In this transversal study, we evaluated 507 children (3–18 years old) using IOS-spirometry (Sentry Suite, Vyntus®). Resistance of all airways (R5), reactance area (AX), resonant frequency (Fres), X5, CX5, difference between R5 and R20 (D5-20), and spirometry parameters were analyzed. Reactance inversion and CX5 prevalence by age range was determined. The mean IOS-Spyrometry values in children with and without CX5 were compared, and correlations with each IOS-spirometry parameter in the age groups were performed. Results: CX5 was found in 83.5% of preschool children, 66.2% of schoolchildren, and 43.3% of adolescents ( p < 0.001). The means of R5, AX, and D5-20 were significantly higher and FEV1 was significantly lower in children with CX5 ( p < 0.05). In all ages, CX5 correlated better than X5 with IOS-spirometry parameters. Conclusion: Reactance inversion and CX5 are frequent in asthmatic children, decrease with age, and correlate more closely than X5 with other IOS-spirometry parameters for evaluating SAD.